Content for health education courses for the college freshmen of the Iloilo School of Arts and Trade a proposal - Martirez, Renee Ruiz 1927- (s.n.], 1968)
This study presents a content outline for the two basic health courses for the college freshman of Iloilo School of Arts and Trades, namely: Personal and Community Health and School Health Education. To carry out the study, a bibliographical research method was used. Experiences incorporated in the study are designed to help prospective teachers of vocational schools in Iloilo the ability to promote, maintain and protect his health and those around him.